Moral Hazard Effects of Corporate Bond Guarantee Purchases: Empirical Evidence from China - Zhang, Xueying; Gao, Shansheng; Jiao, Jian (Journal of Economics and Behavioral Studies, 2018)
This study examines corporate bond guarantees by developing a theoretical model that decomposes the overall impact of a guarantee into signalling and incentive effects and presenting empirical evidence based on data from China’s corporate bond market. Our empirical research yields considerable evidence for the effects we posit in the model and provides some important insights into the problems of adverse selection and moral hazard in China’s bond market. The empirical evidence shows that the bond issuer with lower credit rating are more willing to purchase a bond guarantee and guaranteed bonds have a higher issue spread yield than those non-guaranteed bonds, even though both have the same bond credit rating. Our findings suggest that moral hazard would be better than adverse selection to explain the self- selection of bond guarantees. Prior to bond issuance credit rating signal provides a mechanism to mitigate information inequality, while bond guarantees relieve information asymmetry afterwards.